Study of vascular pattern in human spleen by corrosion cast method - Shashikala R. Londhe (Al Ameen Medical College, 2013)
Background: The aim of the present work was to study the parenchymal distribution of the splenic artery and clarify the avascular planes in human spleens. Observation: Splenic vascular pattern was studied in fifty human spleens, Cellulose Acetate Moulding Granules were used as casting media, injected in the splenic trunk .Soft tissue corrosion was done in the concentrated Potassium Hydroxide and the pattern was studied from obtained cast. Number of segments varied from two to five based on the observation of the terminal and polar splenic branches by corrosion cast and taking account of the ideas ,reported in the literature ,proposed that the spleen is divided in arterial segments and sub segments. Primary segments are territories corresponding to primary branches and polar segments corresponding to polar arteries. Result: There were two primary segments in 90% spleens and three primary segments in 10% spleens. Associate to that in 32% spleens there was superior polar segments, in 56% inferior polar segments and in 12.4% both superior and inferior polar segments. Conclusion: Maximum number of spleens were divided into two lobes and less number of spleens were divided into three lobes, along with that additional lobes were also present when additional arteries present.